Carotid Artery Stenting Using the Walrus Balloon Guide Catheter With Flow Reversal for Proximal Embolic Protection: Technical Description and Single-Center Case Series. Issue 1 (17th January 2023) - Cappuzzo, Justin M.; Monteiro, Andre; Waqas, Muhammad; Baig, Ammad A.; Popoola, Daniel O.; Almayman, Faisal; Khawar, Wasiq I.; Farkash, Zoe G.; Davies, Jason M.; Siddiqui, Adnan H.; Levy, Elad I.; Snyder, Kenneth V.
Abstract : BACKGROUND: The use of modern transfemoral balloon guide catheters (BGC) for flow reversal during carotid artery stenting is scarcely described in the literature but represents a promising and efficient technique for embolic protection. OBJECTIVE: To describe a flow-reversal technique using the Walrus BGC (Q'Apel Medical Inc.) and report our center's experience. METHODS: We performed a retrospective analysis of data for consecutive patients aged 18 years or older who underwent elective carotid artery stenting with the use of flow reversal through the Walrus BGC between July 2020 and September 2021. Patient characteristics, procedural details, and clinical follow-up were evaluated. RESULTS: One hundred and five patients were included. Mean age was 69.8 ± 9.4 years, and 36 (34.3%) were women. The most common comorbidities were hyperlipidemia (76.2%) and hypertension (57.1%). Fifty-nine (56.2%) patients were symptomatic. Ninety-nine (94.3%) patients had stenosis ≥70%. Contralateral stenosis ≥50% was present in 44 patients (41.9%). Distal filters were used after flow reversal was established in 90 patients (85.7%). Angioplasty was performed in 85 patients (80.9%). Stenting was successful in 100% of cases. No periprocedural transient ischemic attacks (TIAs) or strokes occurred. Stroke occurred in 2 patients (1.9%) during the 30-day follow-up period, resulting in 1 (0.9%) death. CONCLUSION: In our experience, this technique was safe, feasible, and efficient, with 100% technical success and no periprocedural thromboembolic complications. More extensive studies are needed to establish the role of proximal protection with flow reversal using modern BGCs.